Cumulative growth and stress responses to the 2018–2019 drought in a European floodplain forest. (20th December 2021) - Schnabel, Florian; Purrucker, Sarah; Schmitt, Lara; Engelmann, Rolf A.; Kahl, Anja; Richter, Ronny; Seele‐Dilbat, Carolin; Skiadaresis, Georgios; Wirth, Christian
Abstract: Droughts increasingly threaten the world's forests and their potential to mitigate climate change. In 2018–2019, Central European forests were hit by two consecutive hotter drought years, an unprecedented phenomenon that is likely to occur more frequently with climate change. Here, we examine tree growth and physiological stress responses (increase in carbon isotope composition; Δδ 13 C) to this consecutive drought based on tree rings of dominant tree species in a Central European floodplain forest. Tree growth was not reduced for most species in 2018, indicating that water supply in floodplain forests can partly buffer meteorological water deficits. Drought stress responses in 2018 were comparable to former single drought years but the hotter drought in 2018 induced drought legacies in tree growth while former droughts did not. We observed strong decreases in tree growth and increases in Δδ 13 C across all tree species in 2019, which are likely driven by the cumulative stress both consecutive hotter droughts exerted. Our results show that consecutive hotter droughts pose a novel threat to forests under climate change, even in forest ecosystems with comparably high levels of water supply. Abstract : In 2018–2019, Central European forests were hit by two consecutive hotter drought years, an unprecedented phenomenon that is likely to occur more frequently with climate change. Here, we examined floodplain forest responses to this consecutive drought and observed unprecedented decreases in tree growth and increases in physiological stress, particularly in the second drought year 2019. Our results show that consecutive hotter droughts pose a novel threat to forests under climate change, even in forest ecosystems with comparably high levels of water supply.